Matching Anonymized User Profiles In Mobile Social Networks (International Journal of Engineering and Computer Science, 2014)
In this project, we try to study user profile matching with privacy-preservation in mobile social networks (MSNs) and introduce new type profile matching protocols. We first propose an explicit Comparison-based Profile Matching protocol (eCPM) that runs between two parties, a leader who initiates the communication and a communicator who responds. The eCPM permits the leader to get the result of attribute comparision between their profiles, while preventing their attribute values disclosure. We then propose implicit Comparison-based Profile Matching protocol (iCPM) that permits the leader to directly get some messages rather than the comparison result from the communicator. The messages unrelated to user profile are often divided into multiple classes by the communicator. The leader implicitly chooses the interested class that is unknown to the communicator. Two messages per each class are prepared by the communicator, and just one message is often obtained by the leader as per the result of comparison on the candidate attribute. We additionally generalize the iCPM to permit complicated comparison criteria spanning multiple attributes as implicit Predicate-based Profile Matching protocol (iPPM). eCPM reveals the comparision result to the leader and provides only conditional anonymity while iCPM provides full anonymity. We enhance eCPM, referred to as eCPM+, by combining the eCPM with a unique prediction-based adaptive anonym amendment strategy.